The Effect of Technical Specifications on Ceramic Tiles used for Cladding of Swimming Pools (The International Journal for Scientific Research, 2024)
The study of the impact of the technical specifications of ceramic tiles requires a comprehensive understanding of the nature of the tiles in order to obtain tiles with special specifications different from ordinary tiles (floors, walls) The research was divided into three chapters and due to the importance of this topic, the researcher wanted to formulate the research issue with the following question: How important are the technical specifications of ceramic tiles used in cladding swimming pools?Relevance: While the importance of the research study is embodied by studying the efficiency of the technical specifications for ceramic tiles, in addition to documenting and enriching the knowledge aspect of the technical specifications.Objectives: While the current study aims to reveal the extent to which the technical specifications of the ceramic tiles used in the cladding of swimming pools are, As for the limits of the research, it was determined through the objective aspect by studying the importance of the technical specifications of ceramic tiles used in the cladding of swimming pools, while the limits of the research included the spatial limit of swimming pools through photographs and the temporal limit of the time period 2014-2024.Methods: The second chapter included the first and its main headings: The specifications of ceramic tiles with architectural cladding, the technique of using cladding in swimming pools, achieving the aesthetic and functional identity of ceramic tiles used in cladding swimming pools The form and organization of the design body using ceramic tiles for swimming pools, the importance of cladding using ceramic tiles in swimming pools, the level of organization of the technical specifications of the design configurations, the design integration of ceramic tiles used in the cladding of swimming pools) The third chapter specialized in defining the topic of research procedures, represented by the research methodology based on the analytical descriptive method, while the research population was based on the purposive selection method.Results: The fourth chapter included the conclusions of the research findings, as well as the recommendations for future proposals and the proposed design of tiles inside swimming pools.Conclusions: It is possible to determine the technical specifications of the tiles in the design and cladding of swimming pools in accordance with the consumer's desire, taking into account the compositional factors in the cladding processes.
Keywords: Ceramic; Tiles; Swimming Pools